2008
DOI: 10.1007/s12072-007-9022-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustained response to peginterferon alfa-2a (40 kD) with or without lamivudine in Asian patients with HBeAg-positive and HBeAg-negative chronic hepatitis B

Abstract: Purpose The 2 reported trials investigated the effectiveness of treatment with peginterferon alfa-2a in Asian patients with chronic hepatitis B (CHB). Methods Patients with HBeAg-positive (n = 708) or HBeAg-negative (n = 332) CHB were enrolled in 2 randomized, double blind, placebo-controlled studies.Patients received peginterferon alfa-2a 180 lg once weekly, peginterferon plus lamivudine 100 mg per day, or lamivudine alone for 48 weeks. Patients were followed up at 6 and 12 months posttreatment. Results Pegin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 56 publications
8
73
1
Order By: Relevance
“…In that phase III trial, 61% of the patients were Asian. The combined response, defined as ALT normalization and HBV DNA \20,000 copies/ml at 6 months after the end of 48 weeks Peg IFN-a-2a therapy, was 45% in Asian patients, which was similar to the 36% in overall patients [43]. Of the Asian patients with a normal ALT at 6 months post-treatment with Peg IFN-a-2a (n = 58) who participated in the long-term follow-up, 78% maintained a normal ALT at 12 months post-treatment [43].…”
Section: Pegylated Interferon Alfa (Peg Ifn-a)supporting
confidence: 53%
See 2 more Smart Citations
“…In that phase III trial, 61% of the patients were Asian. The combined response, defined as ALT normalization and HBV DNA \20,000 copies/ml at 6 months after the end of 48 weeks Peg IFN-a-2a therapy, was 45% in Asian patients, which was similar to the 36% in overall patients [43]. Of the Asian patients with a normal ALT at 6 months post-treatment with Peg IFN-a-2a (n = 58) who participated in the long-term follow-up, 78% maintained a normal ALT at 12 months post-treatment [43].…”
Section: Pegylated Interferon Alfa (Peg Ifn-a)supporting
confidence: 53%
“…In a subsequent phase III trial involving 814 patients ([85% Asian), a 48-week course of Peg IFN-a-2a monotherapy 180 lg once weekly achieved ALT normalization in 41%, HBeAg seroconversion in 32%, HBV DNA level \10 5 copies/ml in 32%, HBV DNA \400 copies/ml in 14%, and HBsAg seroconversion in 3% of the patients assessed 24 weeks after treatment was stopped [42]. Recent analyses of only Asian patients in that phase III trial found a similar HBeAg seroconversion rate of 31% [43]. In a study of Peg IFN-a-2b involving mainly Caucasian patients (79%), a 52-week course (100 lg once weekly for 32 weeks followed by 50 lg weekly for 20 weeks) gave a 26-week sustained HBeAg seroconversion in 29% of patients and HBsAg clearance in 7% of patients [44].…”
Section: Pegylated Interferon Alfa (Peg Ifn-a)mentioning
confidence: 92%
See 1 more Smart Citation
“…PegIFN-a therapy results in HBeAg seroconversion rates of up to 32% and 48%, respectively, when assessed at weeks 24 and 48 post-treatment [43][44][45][46] and sustained after cessation of therapy in the majority (80-90%) of HBeAgpositive patients [47]. Baseline HBV and ALT levels are predictive factors for HBeAg seroconversion [47].…”
Section: Treatment-induced Hbeag Seroconversion and Disease Progressionmentioning
confidence: 99%
“…Baseline HBV and ALT levels are predictive factors for HBeAg seroconversion [47]. On treatment, HBeAg level of \10 Paul Ehrlich Institute Unit/ ml at week 24 and HBsAg level of \1500 IU/ml at week 12 of PegIFN therapy are also reported to favor HBeAg seroconversion [48].…”
Section: Treatment-induced Hbeag Seroconversion and Disease Progressionmentioning
confidence: 99%